A GAME ON THE PERIODIC TABLE - Seetharamappa , J. (SCHOOL SCIENCE, 2012)
Modern pedagogy offers numerous methods to help students participate in the process of discovery. Problem solving is the best known way and is used by both traditional and avant garde teachers of Mathematics and Physics. Games with the principle ‘Learn while playing’ are one of the strategies to make the subject more interesting, to supplement the classroom teaching, to attract truants to the class, to use leisure more effectively and meaningfully and to educate he students according to their natural instincts. In these games, the teacher offers students the excitement of participation, discovery, healthy competition, etc. Gibbs (1975) defines ‘game’ as an activity which is carried out by cooperating or competing decision makers, seeking to achieve their objectives within a framework of rules. One such game is the subject of this article.